Iraq Afghanistan And The Imperialism Of Our Time - Aijaz Ahmad; AHMAD (Aijaz) (New Delhi LeftWord Books, 2004)
Starting immediately after the catastrophe of 11 September 2011 and spanning over the next two years Aijaz Ahmad published a number of long articles on the global imperial design and the wars of occupation that the US launched against Afghanistan and Iraq. Twelve of those articles are included in this book. Together, these articles offer a wealth of factual detail and analysis covering the background of US policy, preparation and execution of the two wars, and the re-emergence of resistance in the two countries. This is followed by the essay "The Imperialism of Our Time". In a major theoretical intervention Aijaz Ahmad argues that the US has pursued a consistent policy since the First World War and the Bolshevik Revolution aimed at the destruction of communism, defeat of Third World nationalism; and establishment of clear and permanent superiority over competitors in the capitalist world.
Keywords: Iraq; Afghanistan